2015 Nutrition country profile: Germany - International Food Policy Research Institute (International Food Policy Research Institute, 2015)
The 193 individual country profiles capture the status and progress of all UN Member States, and the 80+ indicators include a wealth of information on child, adolescent and adult anthropometry and nutritional status, in addition to intervention coverage, food supply, economics, and demography. This tool is particularly useful for nutrition champions at the country-level, as it presents a wide range of evidence needed to assess country progress in improving nutrition and nutrition-related outcomes.